Antidiabetic Effects of the Ethanolic Root Extract of Uvaria chamae P. Beauv (Annonaceae) in Alloxan-Induced Diabetic Rats: A Potential Alternative Treatment for Diabetes Mellitus. (8th November 2018) - Emordi, Jonathan Emeka; Agbaje, Esther Oluwatoyin; Oreagba, Ibrahim Adekunle; Iribhogbe, Osede Ignis
Abstract : Diabetes mellitus has been a menace to mankind from time immemorial. However, a natural product such as U. chamae P. Beauv (Annonaceae) offers alternative treatment for diabetes mellitus. The study aimed at evaluating antidiabetic activity of the ethanolic root extract of U. chamae in alloxan-induced diabetic rats. Diabetes was induced in Sprague Dawley rats after overnight fast with 150 mg/kg alloxan intraperitoneally. After 72 h, those with plasma glucose levels >200 mg/dl were classified as diabetic. Five diabetic rats in each group were treated daily for 14 days orally with 100, 250, and 400 mg/kg of the extract, glibenclamide (71  µ g/kg) and pioglitazone (429  µ g/kg), respectively, while another group was untreated. Control received 0.5 ml of Acacia senegal . Effects of extract on glucose, other biochemical, and hematological parameters were evaluated. α -amylase and α -glucosidase inhibitory activities of extract and its fractions were also evaluated. Percentage inhibition and IC50 values were determined. Diabetic control was achieved on the 7th day of the study with 100, 250, and 400 mg/kg of the extract showing glucose reduction of 72.14%, 78.75%, and 87.71%, respectively. The HDL-cholesterol levels of diabetic rats treated with extracts were significantly increased. Extract and its fractions caused α -amylase and α -glucosidase inhibition. Histologically, pancreas of diabetic rats treated with extract showed regenerated islet cells which were not seen in rats treated with glibenclamide and pioglitazone. This study showed that U. chamae has antidiabetic activity which may be through α -amylase and α -glucosidase inhibition and regeneration of pancreatic beta cells. Also, it may reduce the risk of cardiovascular disease by increasing HDL-cholesterol levels.